Luxury fashion games are so cool! Predicting awareness, perceived quality, and loyalty - Rodrigues, M. B.; Loureiro, S. M. C.; Romero, M. I. R. (Journal of Retailing and Consumer Services, 2024)
Limited research investigates consumers’ perceptions of partnerships between luxury brands and online in-games. Based on the Signaling Theory, this study, first, examines how brand credibility impacts brand awareness, perceived quality, and brand loyalty and, secondly, assesses how brand coolness acts as a mediator between brand credibility and dimensions of brand equity. A sample of 417 participants allowed us to test the hypotheses. The results indicate that higher brand credibility enhances perceptions of coolness. Brand coolness further influences brand equity dimensions and acts as a mediator between brand credibility and brand awareness, brand loyalty, and perceived brand quality. The multigroup analysis for the control variable of generation reveals that there is no significant difference between Generation Y and Generation Z. Regarding the control variables, knowledge of partnerships and luxury consumption, they have a direct significant effect on brand awareness. This study contributes to the literature by revealing the connection between brand credibility and coolness, highlighting their impact on brand quality, awareness, and loyalty. Additionally, it suggests that in-game advertising can enhance brand awareness and loyalty, making it a valuable strategy for luxury brands.